Development of a Web-Based Academic Administration Data Recording Application at Janji Baik Institution - Fitrianto, Adi; Apriansyah, Carli; Wahyudi, Anderson Hendra (Jurnal Pengabdian Masyarakat Progresif Humanis Brainstorming, 2024)
Education is a crucial factor in the development of a country's human resources and is essential for all segments of society, both the privileged and the underprivileged. Sekolah Janji Baik was established to facilitate underprivileged children at risk of dropping out of school, including street children, buskers, and other vulnerable groups. With a free and digital-based concept, this school enables students from limited economic backgrounds to continue their education. However, academic operations are not yet integrated into a single digital system, causing inefficiencies in the process of data input, retrieval, and presentation. In this community service project, MNC University focuses on developing an academic administration application with features for recording student data, teacher data, academic years, student course registration, subjects, and assessments. This application is built using the PHP programming language with the Laravel framework and MySQL database. The methodology includes system needs analysis, design, development, testing, and implementation. The result of this community service is the creation of an academic administration application that is expected to improve the operational efficiency of Sekolah Janji Baik in recording academic data.